Abnormal gray matter volume and impulsivity in young adults with Internet gaming disorder. (8th September 2017) - Lee, Deokjong; Namkoong, Kee; Lee, Junghan; Jung, Young‐Chul
Abstract: Reduced executive control is one of the central components of model on the development and maintenance of Internet gaming disorder (IGD). Among the various executive control problems, high impulsivity has consistently been associated with IGD. We performed voxel‐based morphometric analysis with diffeomorphic anatomical registration by using an exponentiated Lie algebra algorithm (DARTEL) to investigate the relationship of gray matter abnormalities to impulsivity in IGD. Thirty‐one young male adults whose excessive Internet gaming began in early adolescence, and 30 age‐matched male healthy controls were examined. IGD subjects showed smaller gray matter volume (GMV) in brain regions implicated in executive control, such as the anterior cingulate cortex and the supplementary motor area. The GMVs in the anterior cingulate cortex and the supplementary motor area were negatively correlated with self‐reporting scales of impulsiveness. IGD subjects also exhibited smaller GMV in lateral prefrontal and parietal cortices comprising the left ventrolateral prefrontal cortex and the left inferior parietal lobule when compared with healthy controls. The GMVs in the left ventrolateral prefrontal cortex were negatively correlated with lifetime usage of Internet gaming. These findings suggest that gray matter abnormalities in areas related to executive control may contribute to high impulsivity of young adults with IGD. Furthermore, alterations in the prefrontal cortex were related with long‐term excessive Internet gaming during adolescence. Abstract : Young males with Internet gaming disorder showed smaller gray matter volume in executive control‐related brain regions including the anterior cingulate cortex and the ventrolateral prefrontal cortex. Lower gray matter volume in the anterior cingulate cortex correlated with higher impulsivity. Lower gray matter volume in the ventrolateral prefrontal cortex correlated with longer lifetime usage of Internet gaming.